2007
DOI: 10.1128/iai.01571-06
|View full text |Cite
|
Sign up to set email alerts
|

The Capsule Encoding theviaBLocus Reduces Interleukin-17 Expression and Mucosal Innate Responses in the Bovine Intestinal Mucosa during Infection withSalmonella entericaSerotype Typhi

Abstract: The viaB locus contains genes for the biosynthesis and export of the Vi capsular antigen of Salmonella enterica serotype Typhi. Wild-type serotype Typhi induces less CXC chemokine production in tissue culture models than does an isogenic viaB mutant. Here we investigated the in vivo relevance of these observations by determining whether the presence of the viaB region prevents inflammation in two animal models of gastroenteritis. Unlike S. enterica serotype Typhimurium, serotype Typhi or a serotype Typhi viaB … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
100
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 89 publications
(105 citation statements)
references
References 67 publications
5
100
0
Order By: Relevance
“…Expression of the viaB locus in S. Typhimurium impairs TLRdependent induction of tumour necrosis factor (TNF)-a and IL-6 in murine bone marrow-derived macrophages in vitro as well as TNF-a and inducible nitric oxide synthase production following intraperitoneal infection of mice . Furthermore, Vi expression in S. Typhimurium reduced IL-17 and GROa expression and fluid accumulation in bovine-ligated ileal loops and streptomycinpretreated mice, whereas such responses were improved when an S. Typhi viaB mutant was tested relative to the parent strain (Raffatellu et al 2007). The viaB locus may aid evasion of TLR-mediated detection by a second mechanism, as a regulatory gene encoded in the locus (tviA) can repress the transcription of the master regulators of flagella expression.…”
Section: Molecular Basis Of Systemic Virulencementioning
confidence: 99%
“…Expression of the viaB locus in S. Typhimurium impairs TLRdependent induction of tumour necrosis factor (TNF)-a and IL-6 in murine bone marrow-derived macrophages in vitro as well as TNF-a and inducible nitric oxide synthase production following intraperitoneal infection of mice . Furthermore, Vi expression in S. Typhimurium reduced IL-17 and GROa expression and fluid accumulation in bovine-ligated ileal loops and streptomycinpretreated mice, whereas such responses were improved when an S. Typhi viaB mutant was tested relative to the parent strain (Raffatellu et al 2007). The viaB locus may aid evasion of TLR-mediated detection by a second mechanism, as a regulatory gene encoded in the locus (tviA) can repress the transcription of the master regulators of flagella expression.…”
Section: Molecular Basis Of Systemic Virulencementioning
confidence: 99%
“…Whereas mice normally develop few inflammatory changes in the intestinal mucosa during S. typhimurium infection, pretreatment with streptomycin drastically exacerbates neutrophil influx and inflammation in the cecal mucosa 29 . By using this model, we have previously shown that Il-17 mRNA expression is increased 150-fold in the cecal mucosa of streptomycin-pretreated mice by 48 h after S. typhimurium infection 30 . To assess the importance of IL-17 in controlling S. typhimurium infection, we pretreated two groups of six IL-17 receptor-deficient mice (Il17ra −/− mice) bred on a C57BL/6 background with streptomycin and inoculated them with S. typhimurium or sterile LB broth.…”
Section: Il-17 Deficiency Accelerates Salmonella Disseminationmentioning
confidence: 99%
“…We streptomycin-pretreated and orally infected groups of eight female C57BL/6 mice or six female Il17ra −/− mice (B6.IL-17R mice, Taconic), aged 8-10 weeks, with S. typhimurium as described previously 30 . At 48 h after infection, we killed the mice and collected the organs for mRNA isolation and bacteriology.…”
Section: Animal Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…The primers used in these studies are as follow: cyclophilin A, 17 MMP-2, 17 MMP-8, 17 MMP-9, 17 TIMP-2, 17 IFN-g 17 and IL-17. 52 Statistical analysis >Data were analyzed using unpaired or paired Student's t-tests, Mann-Whitney U-test for nonparametric data, one-way analysis of variance (ANOVA) or twoway ANOVA as indicated in the text or figure legends. Pp0.05 was considered significant.…”
Section: Rna Isolation and Real-time Pcrmentioning
confidence: 99%